Peningkatan Hasil Belajar PAK dan BP Melalui Pembelajaran Berbasis PBL Kelas 7 Fase D di SMP N 2 Tebing Tinggi - Erwita Emiliana Br Sembiring; Anselmus Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The low learning outcomes of students at SMP N 2 Tebing Tinggi in the subject of Catholic Religious Education and Character Building were caused by the monotonous teaching method, it’s the lecture method, which is lack variation. To solve this issue, the researcher applied the Project-Based Learning (PBL) method to improve student learning outcomes. The research question was whether the implementation of PBL can improve learning outcomes in Catholic Religious Education and Character Building. This study used the Classroom Action Research (CAR) method, conducted in two cycles. Each cycle consist of four stages: planning, implementation, observation, and reflection. The topic used in this research is